2020
DOI: 10.1039/d0cc01725f
|View full text |Cite
|
Sign up to set email alerts
|

Smart lanthanide antennas for sensing water

Abstract: 8-Methoxy-4,5-dihydrocyclopenta[de]quinolin-2(1H)-one and quinolin-2(1H)-one phosphonate and carboxylate derivatives are selective antennas exhibiting Eu3+ and Tb3+ luminescence, and highly sensitive water sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The luminescence of lanthanides being unique in its own nature has made them applicable as lasers, 1 sensors, 2 , 3 luminescent materials, 4 8 luminescence based tools for the investigation of cellular environments, 9 and solar energy conversion devices. 10 , 11 The lanthanide emission bands are very sharp and exhibit long emission decay times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminescence of lanthanides being unique in its own nature has made them applicable as lasers, 1 sensors, 2 , 3 luminescent materials, 4 8 luminescence based tools for the investigation of cellular environments, 9 and solar energy conversion devices. 10 , 11 The lanthanide emission bands are very sharp and exhibit long emission decay times.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence of lanthanides being unique in its own nature has made them applicable as lasers, sensors, , luminescent materials, luminescence based tools for the investigation of cellular environments, and solar energy conversion devices. , The lanthanide emission bands are very sharp and exhibit long emission decay times . The direct optical excitation of lanthanide metal ions results in poor emission quantum yields due to lower absorptivity coefficients in the UV–Visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the boric acid exhibits a strong affinity to fluoride ions, while its interaction with other anions is relatively weak, making it perfect for fluoride selective sensing. Reports on enhancing antenna effect resulted in "turn-on" sensing are rather few comparing to the "turn-off" mechanism discussed above (Karmakar et al, 2019;Fueyo-González et al, 2020;Min et al, 2020;Wang et al, 2020;Yue et al, 2020). However, it is obvious that "turn-on" sensors have advantages over the "turn-off" sensors, especially in the quantitative determination of an analyte in low concentration (Luo et al, 2020).…”
Section: Ratiometric Fluorescent Sensing Mechanismsmentioning
confidence: 99%
“…Reports on enhancing antenna effect resulted in “turn-on” sensing are rather few comparing to the “turn-off” mechanism discussed above ( Karmakar et al, 2019 ; Fueyo-González et al, 2020 ; Min et al, 2020 ; Wang et al, 2020 ; Yue et al, 2020 ). However, it is obvious that “turn-on” sensors have advantages over the “turn-off” sensors, especially in the quantitative determination of an analyte in low concentration ( Luo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this field, we have recently reported the discovery of the small and simple structure lanthanide antenna in organic solvents 1a ( Scheme 1 ). 38 The lanthanide sensitization by 1a is quenched by H 2 O addition, setting the basis for its demonstrated application as a H 2 O sensor. In our screening for potential lanthanide antennas, we observed that the free acid 1b ( 39 ) ( Scheme 1 ) was also able to sensitize the emission of Tb 3+ and more extensively Eu 3+ in H 2 O.…”
mentioning
confidence: 99%